Transformação digital em modelos de negócios PMEs: proposição de um framework integrado para e-business - Soares, Marcus Demétrius de Mello (Universidade do Vale do Rio dos Sinos, 2022)
This study aims to present two fields of research, business models and the relationship with digital transformation. The focus of the study was directed toward understanding the requirements for digital transformation of small and medium-sized businesses, with the intent of building a framework to integrate components in an Ebusiness process for any existing business model. Design Science Research was used as the research method. The process of validating the requirements was evolving through the literature review, the field research with digital companies, and the focus group and its strategic players. Thus, the present challenge in this research was to seek an understanding that digital transformation goes much further than a digitalization process through technology, but rather, a path of change focused on a culture of transformation with people. Thus, seeking to contribute to the academic and business field, a framework was developed with a broader concept and integrated into a development and deployment method, called Digital Transformation System Framework: ASSESSMENT, DEVELOPMENT, EXECUTION, PIVOT (ADEP). The researcher by verifying findings during the research process and deepening the understanding of the scientific tool (DSR), developed an artifact that addresses two potentially applicable objectives, being the analysis and understanding of key Digital Transformation requirements, and the Development and Deployment Method through a structured roadmap.
Keywords: Transformação digital; E-business; Business model; Design science research; Digital transformation system framework; ACCNPQ::Ciências Sociais Aplicadas::Administração